Nationalism in Iran : updated through 1978 - Cottam, Richard W. (Pittsburgh, Pa. : University of Pittsburgh Press, 1979)
For a brief period in the early 1950s, Iranian nationalism captured the world's attention as, under the leadership of Mohammad Mossadeq, the Iranian National Movement tried to liberate Iran from British imperialism. Regarding nationalism as a major determinant of the attitudes and loyalties of those who embrace it, Cottam analyzes the complex religious, national, and social values at work within Iran and examines, more generally, the turbulence of nationalism in developing states and its perplexing problems for American foreign policy. In a new 40-page chapter, added in 1978, Cottam updated his pioneering study by examining the condition of Iran fifteen years after his first analysis-from its rapid economic growth as an oil producer to Shah Mohammad Reza Pahlavi's unsuccessful efforts to rouse nationalistic sentiment in his favor.
Front Matter -- Table of Contents -- ACKNOWLEDGMENT -- INTRODUCTION -- 1 THE BACKGROUND -- 2 COHESIVE BASE FOR NATIONALISM -- 3 SOCIAL BASE FOR NATIONALISM -- 4 NATIONALISM AND THE TRIBES -- 5 KURDISH NATIONALISM IN IRAN -- 6 NATIONALISM AND THE NON-MOSLEM MINORITIES -- 7 NATIONALISM AND LOCAL PARTICULARISM -- 8 SEPARATIST MOVEMENTS -- 9 AZERBAIJAN: PROVINCE OR NATION? -- 10 RELIGIO-NATIONALISM AND PAN-ISLAM -- 11 EARLY IMPERIALISM: THE GENESIS OF NATIONALIST MYTHOLOGY -- 12 IMPERIALISM AND NATIONALISM: CONFRONTATION -- 13 MODERN IMPERIALISM: THE REVIVAL OF NATIONALIST MYTHOLOGY -- 14 LIBERAL NATIONALISM: BIRTH AND ECLIPSE -- 15 LIBERAL NATIONALISM: BRIEF TRIUMPH -- 16 "POSITIVE" NATIONALISM AND ROYAL DICTATORSHIP -- 17 LIBERAL NATIONALISM: THE FUTURE -- 18 FIFTEEN YEARS LATER -- INDEX.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Nationalism -- Iran; Iran -- Politics and government; Nationalisme -- Iran; Iran -- Politique et gouvernement; POLITICAL SCIENCE / General; Nationalism; Politics and government; Iran; Nationalism -- Iran; Iran -- Politics and government